Norfloxacin is more effective than Rifaximin in avoiding bacterial translocation in an animal model of cirrhosis. (13th September 2017) - Gómez‐Hurtado, Isabel; Gimenez, Paula; García, Irma; Zapater, Pedro; Francés, Rubén; González‐Navajas, José M.; Manichanh, Chaysavanh; Ramos, José M.; Bellot, Pablo; Guarner, Francisco; Such, José
Abstract: Background & Aims: Norfloxacin administration is useful in preventing bacterial infections in cirrhosis but associated to the generation of resistant species. Rifaximin is known to reach high concentrations in the intestinal lumen without generating relevant resistance in the intestinal flora. Our aim was to compare the effect of Norfloxacin and Rifaximin on intestinal flora composition, bacterial translocation and survival in cirrhotic rats. Methods: Cirrhosis was induced in rats by oral administration of CCl4 . Animals were divided into three groups: only CCl4 (group I, n = 10); CCl4 + Norfloxacin (group II, n = 17) and CCl4 + Rifaximin (group III, n = 14). Gut bacterial composition, bacterial translocation and cytokine levels were measured. Results: Forty‐one rats were finally included. The incidence of viable and non‐viable bacterial translocation was significantly reduced in animals receiving Norfloxacin; Rifaximin also decreased the incidence of viable and non‐viable bacterial translocation, but did not reach statistical significance. Serum TNF‐α levels were significantly lower in antibiotic groups. Norfloxacin modified intestinal microbiota, depleting significantly more pathobionts than Rifaximin. Conclusion: Norfloxacin is more effective than Rifaximin in preventing bacterial translocation in rats with cirrhosis probably because of its capacity to reduce pathobionts from intestinal microbiota.